Underwater bonding method

By using a two-part composition method, the cyanoacrylate adhesive can quickly and firmly adhere the substrate under water, solving the problems of unstable bonding and premature curing in the prior art, and achieving efficient underwater bonding effect.

CN119731230APending Publication Date: 2025-03-28HENKEL KGAA
View PDF 29 Cites 0 Cited by

Patent Information

Application Number
CN202380060086.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-09
Filing Date
2023-06-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing cyanoacrylate adhesives are difficult to distribute and cure under water, resulting in unsolid bonding, sensitive to water, and prone to premature curing.

Method used

The method of a two-part composition is employed, wherein the first part comprises a cyanoacrylate component and a cationic catalyst, and the second part comprises a cationically curable component such as an epoxy component and an initiator component, so that the composition is cured under water.

Benefits of technology

The substrate is quickly and firmly bonded underwater, avoiding premature curing problems, and maintaining the bonding strength for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005273374700000061
    Figure BDA0005273374700000061
  • Figure BDA0005273374700000071
    Figure BDA0005273374700000071
  • Figure BDA0005273374700000072
    Figure BDA0005273374700000072
Patent Text Reader

Abstract

The present invention discloses a method of bonding substrates under water, the method comprising applying a cyanoacrylate composition under water to at least one substrate, and curing the composition under water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention provides a method for underwater bonding via a curable cyanoacrylate composition. Background Art

[0002] Curable compositions such as cyanoacrylate adhesives are recognized for their excellent ability to rapidly bond to a variety of substrates, typically within minutes and, depending on the particular substrate, often within seconds.

[0003] Cyanoacrylate adhesive compositions are well known and widely used as fast-setting instant adhesives for a variety of applications. See HV Coover, DW Deifus and JT O'Connor, "Cyanoacrylate Adhesives" in Handbook of Adhesives, 27, 463-77, I. Skeist, ed., Van Nostrand Reinhold, New York, 3rd ed. (1990). See also GH Millet, "Cyanoacrylate Adhesives" in Structural Adhesives: Chemistry and Technology, SR Hartshorn, ed., Plenum Press, New York, p. 249-307 (1986).

[0004] Cyanoacrylate adhesive compositions are well suited for curing in air. Beneficially, these compositions reach handling strength within seconds when cured in air and reach >60% strength within 1 minute when cured in air.

[0005] The polymerization of cyanoacrylates is initiated by nucleophilic species present on most surfaces under normal atmospheric conditions. Initiation by surface chemistry means that sufficient initiating species are present when two surfaces are in intimate contact with a small layer of cyanoacrylate between the two surfaces. Under these conditions, a strong bond is obtained in a short period of time. Therefore, cyanoacrylates generally act as instant adhesives in nature.

[0006] Cyanoacrylate adhesive compositions are not traditionally used for underwater applications because cyanoacrylate adhesive compositions are difficult to dispense underwater. It should be understood that underwater means that the substrates to be bonded are completely immersed in water. The water is in contact with the substrate. As used herein, underwater does not refer to a situation where the substrate is underwater but not in contact with the water, for example, underwater does not refer to a situation where the substrates are placed in a waterproof container and the container is in contact with water, while the substrates are not in contact with the water because the waterproof container keeps them dry. In particular, the present invention is directed to methods of using cyanoacrylate adhesives dispensed from a container while underwater. In such a situation, the cyanoacrylate adhesive is dispensed onto the substrate surface through the water, and the substrate surface is also in contact with the water.

[0007] Dispensing a cyanoacrylate adhesive composition underwater causes the composition to react with water, and the composition may prematurely cure before being applied to the substrate to which it is intended to be bonded. In fact, cyanoacrylate compositions are known to be sensitive to water, and in some cases, even trace amounts of water can cause premature curing, such as during storage for subsequent use.

[0008] Cyanoacrylate adhesive performance, particularly durability, often becomes problematic when exposed to water. Bonds formed using cured cyanoacrylate compositions may be susceptible to the effects of water. For example, when exposed to water, the bond formed may eventually fail due to degradation of the cured cyanoacrylate composition over time. Typically, exposure to water results in a loss of bond strength over time.

[0009] It is also possible that the cyanoacrylate adhesive composition when dispensed underwater is partially cured when applied to a first substrate but prior to being joined to a second substrate. Although a bond may be formed between the substrates in this case, the bond will be weak because the composition has been partially cured prior to the substrates being joined.

[0010] To overcome these problems, the cyanoacrylate adhesive composition may typically be applied to the substrate in air and the bonded substrates then placed underwater.

[0011] For applications where the properties of the cyanoacrylate adhesive composition would be beneficial, underwater bonding using the cyanoacrylate adhesive composition would be advantageous. In situations where it is difficult to remove a substrate from the water, it would be beneficial to dispense and cure the cyanoacrylate adhesive composition underwater. For example, when performing repairs or maintenance on a vessel or installing new parts (such as sensors) to a vessel, it would be beneficial to use the cyanoacrylate adhesive composition to bond parts of the vessel that are underwater to eliminate the need to remove the vessel from the water, which can be challenging and costly and require the vessel to be returned to land. Similarly, it would be useful to be able to perform underwater maintenance and repairs, or install parts to structures that are completely or partially underwater (such as oil rig equipment, bridges, pipelines, etc.).

[0012] Coral reefs are formed by colonies of coral polyps. The skeleton of the coral polyps is formed by calcium carbonate, and the coral polyps are held together by their calcium carbonate skeletons. Most coral reefs are built by stony coral polyps (also known as Scleractinia). Stony corals secrete hard calcium carbonate exoskeletons that protect and support coral reefs. Coral reefs may be damaged by, for example, overnutrition or ocean acidification. Coral transplantation is considered a possible way to help coral reefs recover from damage. Healthy coral polyps are transplanted from healthy reefs to damaged reefs. Healthy coral polyps may contribute to the repair of coral reefs. Cement or epoxy resin is used to fix the transplanted coral polyps to their new location. If the transplanted coral polyps fall off from the place where they have been transplanted, the coral polyps will die and the transplantation will be unsuccessful. In these methods, the distribution, application and curing of epoxy resins may take a long time. This means that the user (usually a diver) must spend an extended period of time underwater, which is costly and may be dangerous.

[0013] Dizon et al. compared the use of cyanoacrylate adhesive gel compositions, epoxy putty, and marine epoxy resins to determine their suitability for coral polyp attachment. Dizon et al. applied the cyanoacrylate adhesive compositions over water and then submerged the coral polyps underwater. Dizon et al. found that while the cyanoacrylate adhesive compositions were the easiest to manipulate, they rated poorly in the key areas of effectiveness of attachment and graft self-attachment.

[0014] It would be beneficial to provide an adhesive composition that has the benefits of a cyanoacrylate composition and is effective in attaching coral polyps during transplantation.

[0015] It would be beneficial to provide an alternative adhesive that can: (1) be dispensed while submerged; (2) remain uncured for a sufficient time to allow application to the substrates to be bonded; (3) subsequently cure, desirably with a short cure time; (4) form a high strength bond; and (5) maintain bond strength. All of the foregoing need to be achieved underwater. Summary of the invention

[0016] In one aspect, the present invention provides a method of bonding a substrate underwater, the method comprising:

[0017] Applying a cyanoacrylate composition underwater to at least one substrate, wherein the cyanoacrylate composition comprises:

[0018] The first part comprises:

[0019] a cyanoacrylate component and a cationic catalyst; and

[0020] The second part comprises:

[0021] a cationically curable component, such as an epoxy component, an episulfide component, an oxetane component, and combinations thereof, and an initiator component, and

[0022] The composition is allowed to cure underwater.

[0023] Underwater means that the substrate is immersed in water so that the water is in contact with the substrate simultaneously when the composition is applied. For example, the substrates are not in a waterproof container so that they are not directly exposed to water. Beneficially, this method allows underwater bonding in applications that have traditionally been excluded due to the inability to remove and dry the components prior to bonding.

[0024] Beneficially, the composition applied in the method can be dispensed while submerged, remain uncured for a sufficient time to allow application to the substrate to be bonded; and subsequently cured with a short cure time. Beneficially, the cured composition that can be cured underwater forms a high-strength bond and maintains the bond strength over time. Desirably, the composition has a sufficiently long open time so that it can be dispensed, applied, and bonded to one or more substrates before the composition cures, but has a faster cure time than the composition used in the previous method in order to minimize the time the user must spend underwater.

[0025] The cyanoacrylate hybrid compositions disclosed herein can be utilized to overcome the perceived disadvantages of cyanoacrylate compositions for bonding underwater substrates. All desirable properties of the present invention refer to those properties of the composition in an underwater environment. The composition of the present invention remains in place when dispensed. The composition of the method can be dispensed underwater, e.g., there is no premature curing upon initial contact with water, which would prevent the composition from being dispensed onto a substrate. It is possible that a skin may form where the water is initially contacted, but there is no curing that would prevent the dispensed volume of the composition. The composition of the method can have a suitable viscosity to allow it to be dispensed. The composition can have a suitable buoyancy. For example, it is suitable that the composition of the method will not be dislodged from place by forces caused by normal water flow.

[0026] The composition can be dispensed underwater and used in a method of bonding underwater substrates. While not wishing to be bound by theory, it is believed that the combination of the cure speed modulation caused by the epoxy portion of the hybrid and the inherent high viscosity of the material can impart this unexpected open time in an aqueous environment. The first part of the composition can have a cone and plate viscosity of 4000 to 7000 mPa.s. The second part can have a viscosity of 25000 to 40000 mPa.s. Both viscosities are measured according to ASTM D7867.

[0027] Additionally, the cationically curable component can initiate the cure of the cyanoacrylate.

[0028] The cyanoacrylate component of the cyanoacrylate composition applied in the method may be selected from the group consisting of substances within the structure H2C=C(CN)-COOR, wherein R is selected from C 1-15 Alkyl, C 2-15 Alkoxyalkyl, C 3-15 Cycloalkyl, C 2-15 Alkenyl, C 6-15 Aralkyl, C 5-15 Aryl, C 3-15 Allyl and C 1-15 Haloalkyl, for example, wherein the cyanoacrylate component comprises ethyl 2-cyanoacrylate ("ECA").

[0029] The cyanoacrylate component should be included in the Part A composition in an amount ranging from about 50% to about 99.98% by weight of the total composition, desirably from about 65% to about 85% by weight, particularly desirably from about 75% to about 97% by weight.

[0030] As the cationic catalyst included in the A part composition of the two-part adhesive system, a hard cation non-nucleophilic anion catalyst should be used. The example of this type of catalyst includes a salt of lithium and a salt of a metal of the periodic table Group II and a non-nucleophilic acid. This type of non-nucleophilic acid has a pH less than 1.0 when measured in a 10 wt % aqueous solution, and the anion part of this type of acid is indeed easily involved in a replacement reaction with an organic halide. The example of Group II metal salts includes calcium and magnesium. The example of non-nucleophilic acid includes perchloric acid, fluoroboric acid, fluoroarsenic acid, fluoroantimonic acid and fluorophosphoric acid. Therefore, the example of hard cation non-nucleophilic anion salt includes lithium tetrafluoroborate, two (tetrafluoroborate) calcium, two (tetrafluoroborate) magnesium, lithium hexafluorophosphate, two (hexafluorophosphate) calcium, two (hexafluorophosphate) magnesium, lithium hexafluoroantimonate and lithium hexafluoroarsenate.

[0031] Cationic catalysts may also include lanthanide trifluoromethanesulfonates, aryl iodonium salts, aryl sulfonium salts, lanthanum trifluoromethanesulfonate, ytterbium trifluoromethanesulfonate, trimethoxycyclotriboroxine, trimethoxycyclotriboroxine-aluminum acetylacetonate, amine-boron trihalide complexes, quaternary ammonium salts, quaternary phosphonium salts, triaryl sulfonium salts, diaryl iodonium salts, and diazonium salts.

[0032] Another cationic catalyst suitable for use in the Part A composition of the adhesive system herein is a trialkoxycyclotriboroxane curing agent, such as described in U.S. Pat. Nos. 4,336,367 and 6,617,400 (the disclosures of each of which are hereby incorporated herein by reference). Of course, any combination of two or more of these cationic catalysts may also be used.

[0033] Also suitable for use as some or all of the cationic catalysts are boron trifluoride, boron trifluoride etherate, sulfur trioxide (and its hydrolysis products), and methanesulfonic acid, which is commonly used to stabilize cyanoacrylate monomers against anionic polymerization ( See also below) (a known issue with shelf stability).

[0034] Typically, the amount of cationic catalyst will fall within the range of about 0.001% to about 10.00% by weight of the composition, desirably about 0.01% to about 5.00% by weight of the composition, such as about 0.50% to 2.50% by weight of the composition.

[0035] Additives may be included in the Part A composition of the adhesive system to impart physical properties such as improved fixation speed, improved shelf life stability, flexibility, thixotropy, increased viscosity, color, and improved toughness. Thus, such additives may be selected from accelerators, free radical stabilizers, anionic stabilizers, gelling agents, thickeners such as PMMA, thixotropy imparting agents such as fumed silica, dyes such as carbon black, toughening agents, plasticizers, and combinations thereof.

[0036] These additives are discussed in more detail below. However, accelerators and stabilizers are discussed here.

[0037] One or more accelerators may also be used in the adhesive system, particularly in the Part A composition, to accelerate the cure of the cyanoacrylate component. Such accelerators may be selected from calixarenes and oxacalixarenes, silacrowns, crown ethers, cyclodextrins, poly(ethylene glycol) di(meth)acrylates, ethoxylated hydric compounds, and combinations thereof.

[0038] Many of the calixarenes and oxacalixarenes are known and reported in the patent literature. See e.g. U.S. Patent Nos. 4,556,700, 4,622,414, 4,636,539, 4,695,615, 4,718,966, and 4,855,461, the disclosures of each of which are hereby expressly incorporated herein by reference.

[0039] For example, for calixarenes, those of the following structures are useful herein:

[0040]

[0041] Where R 1 is alkyl, alkoxy, substituted alkyl, or substituted alkoxy; R 2 is H or alkyl; and n is 4, 6 or 8.

[0042] One particularly desirable calixarene is tetrabutyltetrakis[2-ethoxy-2-oxoethoxy]calix-4-arene.

[0043] Many crown ethers are known. For example, examples that can be used alone or in combination herein include 15-crown-5, 18-crown-6, dibenzo-18-crown-6, benzo-15-crown-5-dibenzo-24-crown-8, dibenzo-30-crown-10, tribenzo-18-crown-6, asymmetric-dibenzo-22-crown-6, dibenzo-14-crown-4, dicyclohexyl-18-crown-6, dicyclohexyl-24-crown-8, cyclohexyl-12-crown-4, 1,2-decalyl-15-crown-5, 1, 2-naphtho-15-crown-5, 3,4,5-naphthyl-16-crown-5, 1,2-methyl-benzo-18-crown-6, 1,2-methylbenzo-5,6-methylbenzo-18-crown-6, 1,2-tert-butyl-18-crown-6, 1,2-vinylbenzo-15-crown-5, 1,2-vinylbenzo-18-crown-6, 1,2-tert-butyl-cyclohexyl-18-crown-6, asymmetric-dibenzo-22-crown-6, and 1,2-benzo-1,4-benzo-5-oxy-20-crown-7. See also No. 4,837,260 (Sato), the disclosure of which is hereby expressly incorporated herein by reference.

[0044] Many of the silacron ethers are also known and reported in the literature. For example, a typical silacron ether can be represented in the following structure:

[0045]

[0046] Where R 3 and R 4 is an organic group that does not cause polymerization of cyanoacrylate monomers. 5 is H or CH3, and n is an integer between 1 and 4. Suitable R 3 and R 4 Examples of R groups are R groups, alkoxy groups (such as methoxy groups) and aryloxy groups (such as phenoxy groups). 3 and R 4 The radical may contain halogen or other substituents, an example being trifluoropropyl. 4 and R 5 The radical of the group is a basic group (such as amino, substituted amino and alkylamino).

[0047] Specific examples of silacrown ether compounds that can be used in the composition of the present invention include:

[0048]

[0049]

[0050] See e.g.U.S. Patent No. 4,906,317 (Liu), the disclosure of which is hereby expressly incorporated herein by reference.

[0051] Many cyclodextrins can be used in connection with the present invention. For example, those described and claimed in U.S. Pat. No. 5,312,864 (Wenz), the disclosure of which is hereby expressly incorporated herein by reference, as hydroxy derivatives of α-, β-, or γ-cyclodextrins that are at least partially soluble in cyanoacrylates would be suitable choices for use as the accelerator component herein.

[0052] Additionally, poly(ethylene glycol) di(meth)acrylates suitable for use herein include those within the following structure:

[0053]

[0054] Where n is greater than 3, such as in the range of 3 to 12, wherein n is 9 is particularly desirable. More specific examples include PEG200DMA (where n is about 4), PEG 400DMA (where n is about 9), PEG 600DMA (where n is about 14), and PEG 800DMA (where n is about 19), wherein the number ( For example , 400) represents the average molecular weight of the ethylene glycol portion of the molecule (excluding the two methacrylate groups) expressed in grams per mole (ie, 400 g / mol). A particularly desirable PEG DMA is PEG 400 DMA.

[0055] Additionally, among the ethoxylated hydrogen-containing compounds (or ethoxylated fatty alcohols that may be employed), suitable compounds may be selected from those within the following structures:

[0056]

[0057] Among them C m can be a linear or branched alkyl or alkenyl chain; m is an integer from 1 to 30, such as 5 to 20; n is an integer from 2 to 30, such as 5 to 15; and R can be H or an alkyl group, such as C 1-6 alkyl.

[0058] Commercially available examples of such materials include those supplied under the DEHYDOL trade name from Cognis Deutschland GmbH & Co. KGaA, Dusseldorf, Germany (eg, DEHYDOL 100).

[0059] In addition, the accelerator is contained in the following structure:

[0060]

[0061] Where R is hydrogen, C1-6 Alkyl, C 1-6 Alkoxy, alkyl sulfide, haloalkyl, carboxylic acid and esters, sulfinic acid, sulfonic acid and sulfurous acid and esters, phosphinic acid, phosphonic acid and phosphorous acid and esters; Z is a polyether bond; n is 1-12 and p is 1-3 as defined above; R' is the same as R, and g is the same as n.

[0062] Particularly desirable chemicals within this class as accelerator components are:

[0063]

[0064] Wherein the sum of n and m is greater than or equal to 12.

[0065] The accelerator should be included in the composition in an amount ranging from about 0.01 wt % to about 10 wt %, desirably ranging from about 0.1 wt % to about 0.5 wt %, particularly desirably about 0.4 wt % of the total composition.

[0066] Stabilizers useful in the Part A composition of the adhesive system include free radical stabilizers, anionic stabilizers, and stabilizer packages including combinations thereof. The identity and amounts of such stabilizers are well known to those of ordinary skill in the art. See e.g. U.S. Patent Nos. 5,530,037 and 6,607,632, the disclosures of each of which are hereby incorporated herein by reference. Commonly used free radical stabilizers include hydroquinone, while commonly used anionic stabilizers include boron trifluoride, boron trifluoride etherate, sulfur trioxide (and its hydrolysis products) and methanesulfonic acid. As mentioned above, these anionic stabilizers can also be used as a cationic catalyst or a part thereof.

[0067] Section B

[0068] Cationic curable monomers for use in the Part B composition of the adhesive system include epoxy monomers, episulfide monomers, oxetane monomers, and combinations thereof.

[0069] The epoxy monomer used in the B-side composition of the adhesive system includes a variety of epoxy monomers, some of which are aromatic, while others are aliphatic, and still others are cycloaliphatic. Examples of such epoxy monomers include bisphenol F diglycidyl ether (and hydrogenated forms thereof), bisphenol A diglycidyl ether (and hydrogenated forms thereof), bisphenol S diglycidyl ether (and hydrogenated forms thereof), bisphenol E diglycidyl ether (and hydrogenated forms thereof), biphenyl diglycidyl ether (and hydrogenated forms thereof), 4-vinyl-1-cyclohexene diepoxide, butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, limonene diepoxide, α-pinene oxide, hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, aniline diglycidyl ether, propylene glycol diglycidyl ether, cyanuric acid triglycidyl ether, phthalic acid diglycidyl ether, linoleic acid dimer (linoleic acid dimer) diglycidyl ester of bisphenol A, dicyclopentadiene diepoxide, tetrachlorobisphenol A glycidyl ether, 1,1,1-tri(p-hydroxyphenyl)ethane glycidyl ether, tetra(4-hydroxyphenyl)ethane tetraglycidyl ether, epoxy phenol novolac resin, epoxy cresol novolac resin, tetraglycidyl-4,4'-diaminodiphenylmethane, etc.

[0070] Commercially available epoxy resins suitable for use are: polyglycidyl derivatives of phenolic compounds, such as those available from Shell Chemical Co. under the trade names EPON 828, EPON 1001, EPON 1009 and EPON 1031, from Dow Chemical Co. under the trade names DER 331, DER 332, DER 334 and DER 542, from Ciba Specialty Chemicals, Tarrytown, New York under the trade name GY285, and from Nippon Kayaku, Japan under the trade name BREN-S; epoxidized polybutadiene, such as those available from Sartomer under the trade name PolyBD, from Daicel under the trade name EPOLEAD PB 3600, from Nippon EPOXYPRENE 25 and EPOXYPRENE 50 from Sanyo Corporation. Other suitable epoxy resins include polyepoxides prepared from polyols and the like and polyglycidyl derivatives of phenol-formaldehyde novolacs, the latter of which are commercially available from Dow Chemical Company under the trade names DEN 431, DEN 438, and DEN 439. Cresol analogs are also commercially available from Ciba Specialty Chemicals as ECN 1235, ECN 1273, and ECN 1299. SU-8 is a bisphenol A-type epoxy novolac available from Resolution. Of course, cycloaliphatic epoxy resins (such as those available under the CYRACURE trade name) as well as hydrogenated bisphenol and biphenyl type epoxy resins (such as those available under the EPALLOY trade name, as noted) are suitable for use herein.

[0071] Cycloaliphatic epoxy resins contain at least one cycloaliphatic group and at least one oxirane group, typically two oxirane groups. Representative cycloaliphatic epoxy resins include 2-(3,4-epoxy)cyclohexyl-5,5-spiro-(3,4-epoxy)cyclohexane-m-dioxane, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-3,4-epoxy-6-methylcyclohexanecarboxylate, vinylcyclohexane dioxide, bis(3,4-epoxycyclohexylmethyl)adipate, bis(3,4-epoxy-6-methylcyclohexanecarboxylate, 2,6-bis(2,3-epoxypropoxycyclohexyl-p-dioxane), 2,6-bis(2,3-epoxypropoxy)norbornene, diglycidyl ether of linoleic acid dimer, limonene dioxide, α-pinene oxide, 3-vinylcyclohexane ethylene oxide, 3-vinylcyclohexene dioxide, epoxidized poly(1,3-butadiene-acrylonitrile), epoxidized soybean oil, epoxidized castor oil, epoxidized linseed oil, 2,2-bis(3,4-epoxycyclohexyl)propane, dicyclopentadiene dioxide, tricyclopentadiene dioxide, tetracyclopentadiene dioxide, 1,2-epoxy-6-(2,3-epoxypropoxy)hexahydro-4,7-endomethanoid indane, p-(2,3-epoxy ) cyclopentylphenyl-2,3-epoxypropyl ether, 1-(2,3-epoxypropyloxy)phenyl-5,6-epoxyhexahydro-4,7-methanoindan, o-(2,3-epoxy)cyclopentylphenyl-2,3-epoxypropyl ether, 1,2-bis[5-(1,2-epoxy)-4,7-hexahydromethanoindanoxy]ethane, cyclopentenylphenyl glycidyl ether, cyclohexanediol diglycidyl ether, and diglycidyl hexahydrophthalate. Siloxane-functional epoxy resins such as 1,3-bis(3,4-epoxycyclohexyl-2-ethyl)-1,1,3,3-tetramethyldisiloxane and other epoxy-functional linear / cyclic siloxanes (such as those disclosed in U.S. Pat. No. 7,777,064, the disclosure of which is expressly incorporated herein by reference) may also be used. In a specific embodiment, the cycloaliphatic epoxy resin is 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate and 3,4-epoxy-6-methylcyclohexylmethyl-3,4-epoxy-6-methylcyclohexanecarboxylate. Other examples of cycloaliphatic epoxy resins suitable for use herein include those disclosed and described in U.S. Pat. No. 6,429,281 (Dershem), the disclosure of which is hereby expressly incorporated herein by reference.

[0072] Additionally, combinations of epoxy resins are of course also contemplated for use herein.

[0073] The episulfide monomer may simply be the sulfur-containing 3-membered ring form of all or part of the base epoxy monomer.

[0074] The oxetane monomer may be selected from:

[0075]

[0076]

[0077] Oxetanes labeled AC are available from Toa Gosei Co., Ltd., Japan.

[0078] Vinyl ethers may also be included. Vinyl ether monomers may be selected from a number of materials, such as those commercially available under the trade name VEctomer from Vertellus Performance Materials Inc., Greensboro, NC. Examples include VEctomer vinyl ether 4010 [bis-(4-vinyloxybutyl) isophthalate], VEctomer vinyl ether 4060 [bis(4-vinyloxybutyl) adipate], and VEctomer vinyl ether 5015 [tris(4-vinyloxybutyl) trimellitate].

[0079] Epoxy, episulfide, oxetane, and / or vinyl ether monomers can be monomers functionalized with one or more alkoxysilane groups. Examples of such materials include those commercially available from Gelest Inc., Morrisville, PA.

[0080] As discussed above, additives may be included in either or both of the Part A composition or the Part B composition to affect various performance properties.

[0081] Additives may be included in the two-part cationically curable / epoxy hybrid adhesive system to improve the fixation time, including aromatic heterocycles such as pyridines, toluidines, and benzothiazoles, particularly 2-substituted benzothiazoles (where the 2-substituent is an alkyl, alkenyl, alkylbenzyl, alkylamino, alkoxy, alkylhydroxy, ether, thioalkyl, thioalkoxy, or sulfonamide, provided that the amide portion of the sulfonamide does not have a tert-butylamino or morpholinyl group), more particularly such materials as 3,5-dibromopyridine, 3,5-dichloropyridine, N,N-dimethyl-p-toluidine, 2,2-dipyridyl disulfide, 5-chloro-2-methylbenzothiazole, 2-methyl-mercaptobenzothiazole, N,N-dihydroxyethyl-p-toluidine, and tert-butylbenzothiazolesulfonamide. Phenols may also be used, such as 4-methyl-2,2-di-tert-butylphenol and 4-methoxyphenol.

[0082] These additives may be used in amounts of greater than 0 to about 5 wt %, such as from about 0.1 wt % to about 2 wt %.

[0083] Fillers contemplated for optional use include, for example, aluminum nitride, boron nitride, silicon carbide, diamond, graphite, beryllium oxide, magnesium oxide, titanium oxide, silica (such as fumed silica or fused silica), alumina, perfluorinated hydrocarbon polymers (i.e., TEFLON), thermoplastic polymers, thermoplastic elastomers, mica, glass powders, etc. Preferably, the particle size of these fillers will be about 20 microns or less.

[0084] For silicon dioxide, the silicon dioxide may have an average particle diameter of nanoparticle size; that is, having an average particle diameter of the order of 10 -9 The silica nanoparticles may be pre-dispersed in the epoxy resin and may be selected from those available under the trade name NANOPOX from Nanoresins, Germany. NANOPOX is the trade name for a product line of epoxy resins enhanced with silica nanoparticles, which exhibit an excellent combination of material properties. The silica phase consists of surface-modified, synthetic SiO2 nanospheres having a diameter of less than 50 nm and an extremely narrow particle size distribution. The SiO2 nanospheres are agglomerate-free dispersions in the epoxy resin matrix, resulting in low viscosity for resins containing up to 50% by weight of silica.

[0085] Commercially available examples of particularly desirable NANOPOX products for use herein include NANOPOX A610 (40 wt% dispersion in a cycloaliphatic epoxy matrix). NANOPOX products are believed to have particle sizes of about 5 nm to about 80 nm, but manufacturers report less than 50 nm.

[0086] The silica component should be present in an amount ranging from about 1 wt % to about 60 wt %, such as from about 3 wt % to about 30 wt %, desirably from about 5 wt % to about 20 wt %, based on the total weight of the composition.

[0087] Flexibilizers (also known as plasticizers) contemplated for use herein include those that can reduce the T g Such flexibilizers include, for example, polyethers, polyesters, polythiols, polysulfides, etc. If used, the flexibilizer is generally present in the range of about 0.5% to about 30% by weight of the composition.

[0088] The flexibilizer may also be reactive; that is, it may be functionalized so as to react into the cured reaction product. In such cases, hydroxyl-functionalized resins may be used because they tend to co-react with cationically curable components (such as epoxy resins) and thus their use may improve the mechanical properties of the cured product.

[0089] For example, hydroxyl functionalized aliphatic polyester diols provide improved flexibility to the cured composition. A commercially available example of a diol is K-FLEX A307 from King Industries. K-FLEX A307 is reported by the manufacturer as a low viscosity, 100% solid, linear, saturated, aliphatic polyester diol with primary hydroxyl groups. K-FLEX A307 is advertised as having been designed as a flexibility modifier for acrylic / isocyanate and acrylic / melamine systems. Commercial applications are advertised as automotive OEM, automotive refinish, aerospace, industrial maintenance, and plastic coatings.

[0090] Others include: PolyTHF 650 / 1400 / 2000 / 2900 (sold under the trade name TERATHANE); polycaprolactone diols and polycaprolactone triols (Aldrich); polydimethylsiloxane-polycaprolactone diols (such as WAX350OH D from Wacker); K-PURE CDR-3441, CDR-3319 (King Industry); primary or secondary hydroxyl terminated polybutadiene / hydrogenated polybutadiene (Cray Valley, such as PolyBd / Krasol materials); and hydrogenated castor oil, such as THIXCIN R and THIXCIN E (Elementis Specialties), and the POLYCIN series (Vertellus Specialties Inc.). Other useful flexibilizers include polyurethane methacrylate terminated resins and precursors of these materials (such as 3-methyl-5-pentanediol-adipic acid copolymer).

[0091] Toughening agents contemplated for use particularly in the Part A compositions include elastomeric polymers selected from the group consisting of elastomeric copolymers of lower olefin monomers and (i) acrylates, (ii) methacrylates or (iii) vinyl acetate, such as acrylic rubbers; polyester urethanes; ethylene vinyl acetate; fluorinated rubbers; isoprene-acrylonitrile polymers; chlorosulfinated polyethylene; and homopolymers of polyvinyl acetate have been found to be particularly useful. See alsoNo. 4,440,910 (O'Connor), the disclosures of each of which are hereby expressly incorporated herein by reference]. The elastomeric polymers are described in the '910 patent as homopolymers of alkyl esters of acrylic acid, copolymers of additional polymerizable monomers (such as lower olefins) with alkyl or alkoxy esters of acrylic acid, and copolymers of alkyl or alkoxy esters of acrylic acid. Other unsaturated monomers that can be copolymerized with the alkyl and alkoxy esters of acrylic acid include dienes, reactive halogen-containing unsaturated compounds, and other acrylic monomers (such as acrylamide).

[0092] For example, one group of such elastomeric polymers is a copolymer of methyl acrylate and ethylene manufactured by DuPont under the name VAMAC (such as VAMAC N123 and VAMAC B-124). DuPont reports that VAMAC N123 and VAMAC B-124 are masterbatches of ethylene / acrylic elastomers. The DuPont material VAMAC G is a similar copolymer, but does not contain fillers and stabilizers to provide color. VAMAC VCS rubber can be considered as the base rubber from which other members of the VAMAC product line are compounded. VAMAC VCS (also known as VAMAC MR) is the reaction product of a combination of ethylene, methyl acrylate and a monomer having a carboxylic acid cure site, which once formed is then substantially free of processing aids (such as release agents octadecylamine, complexed organic phosphates, and / or stearic acid) and antioxidants (such as substituted diphenylamines).

[0093] Recently, DuPont has provided the market with trade names VAMAC VMX 1012 and VCD 6200, which are rubbers made of ethylene and methyl acrylate. It is believed that VAMAC VMX 1012 rubber has little or almost no carboxylic acid in the polymer backbone. Like VAMAC VCS rubber, VAMAC VMX 1012 and VCD 6200 rubbers are substantially free of processing aids (such as release agent octadecylamine, complexed organic phosphates, and / or stearic acid) and antioxidants (such as substituted diphenylamines), as described above. All of these VAMAC elastomeric polymers are available herein.

[0094] In addition, vinylidene chloride-acrylonitrile copolymers [see U.S. Pat. No. 4,102,945 (Gleave)] and vinyl chloride / vinyl acetate copolymers [see U.S. Pat. No. 4,444,933 (Columbus)] may be included in the Part A composition. Of course, the disclosures of each of these U.S. patents are hereby incorporated herein by reference in their entirety.

[0095] Copolymers of polyethylene and polyvinyl acetate commercially available from LANXESS Limited under the trade name LEVAMELT are useful.

[0096] A range of LEVAMELT agents are available and include, for example, LEVAMELT 400, LEVAMELT 600 and LEVAMELT 900. The difference in the LEVAMELT products is the amount of vinyl acetate present. For example, LEVAMELT 400 contains an ethylene-vinyl acetate copolymer containing 40% by weight of vinyl acetate. The LEVAMELT brand product is provided in granular form. The granules are almost colorless and are sprinkled with silicon dioxide and talcum powder. The LEVAMELT brand product consists of methylene units that form a saturated backbone with pendant acetate groups. The presence of a fully saturated backbone shows that LEVAMELT is a particularly stable polymer. It does not contain any reactive double bonds that would make conventional rubber susceptible to aging reactions, ozone and ultraviolet light. The saturated backbone is reported to enhance it.

[0097] Interestingly, depending on the polyethylene / polyvinyl acetate ratio, the solubility of these LEVAMELT elastomers varies in the different monomers, and due to the solubility, the toughening ability also changes.

[0098] LEVAMELT elastomers are available in pellet form and are easier to formulate than other known elastomeric toughening agents.

[0099] VINNOL brand surface coating resins commercially available from Wacker Chemie AG, Munich, Germany represent a broad range of vinyl chloride-derived copolymers and terpolymers that are advertised for use in various industrial applications. The main components of these polymers are different combinations of vinyl chloride and vinyl acetate. The terpolymers of the VINNOL product line also contain carboxyl or hydroxyl groups. These vinyl chloride / vinyl acetate copolymers and terpolymers may also be used.

[0100] VINNOL surface coating resins with carboxyl groups are terpolymers of vinyl chloride, vinyl acetate and dicarboxylic acids which differ in their molar composition as well as in the degree of polymerization and the polymerization process. These terpolymers are reported to exhibit excellent adhesion, in particular on metal substrates.

[0101] VINNOL surface coating resins having hydroxyl groups are copolymers and terpolymers of vinyl chloride, hydroxyacrylates and dicarboxylic acid esters which differ in their composition and degree of polymerization.

[0102] VINNOL surface coating resins without functional groups are copolymers of vinyl chloride and vinyl acetate with variable molar composition and degree of polymerization.

[0103] Rubber particles, especially those having a relatively small average particle size ( For example , less than about 500 nm or less than about 200 nm). The rubber particles may or may not have a shell as is common to known core-shell structures. In the case of rubber particles having a core-shell structure, such particles typically have a core surrounded by a shell, the core being composed of a rubber having elastomeric or rubber-like properties (i.e., a glass transition temperature below about 0°C, example like The shell is composed of a polymer material having a glass transition temperature above ambient temperature, For example For example, the core may be composed of a diene homopolymer or copolymer (e.g., a homopolymer of butadiene or isoprene; a copolymer of butadiene or isoprene with one or more ethylenically unsaturated monomers (e.g., vinyl aromatic monomers, (meth)acrylonitrile, (meth)acrylates, etc.); and the shell may be composed of a polymer or copolymer of one or more monomers such as (meth)acrylates ( For example , methyl methacrylate), vinyl aromatic monomers ( For example , styrene), vinyl cyanide ( For example , acrylonitrile), unsaturated acids and anhydrides ( example like , acrylic acid), (meth) acrylamide, etc., which have a suitably high glass transition temperature. Other rubbery polymers may also be suitably used for the core, including polybutyl acrylate or polysiloxane elastomers ( For example , polydimethylsiloxane, especially cross-linked polydimethylsiloxane).

[0104] The rubber particles may consist of more than two layers ( For example In one embodiment of the invention, the rubber particles used consist of a core and at least two concentric shells having different chemical compositions and / or properties. Either the core or the shell, or both the core and the shell, may be crosslinked ( For example The shell may be grafted onto the core. The polymer constituting the shell may carry one or more different types of functional groups ( For example , epoxy group), said functional group being capable of interacting with other components of the composition of the present invention.

[0105] Typically, the core will comprise from about 50% to about 95% by weight of the rubber particle, while the shell will comprise from about 5% to about 50% by weight of the rubber particle.

[0106] Preferably, the size of the rubber particles is relatively small. For example, the average particle size can be about 0.03 microns to about 2 microns or about 0.05 microns to about 1 micron. The average diameter of the rubber particles can be less than about 500nm, such as less than about 200nm. For example, the core-shell rubber particles can have an average diameter in the range of about 25nm to about 200nm.

[0107] Methods of preparing rubber particles having a core-shell structure are well known in the art and are described, for example, in U.S. Pat. Nos. 4,419,496, 4,778,851, 5,981,659, 6,111,015, 6,147,142, and 6,180,693 (each of which is incorporated herein by reference in its entirety).

[0108] Rubber particles with a core-shell structure can be prepared in the form of a masterbatch, wherein the rubber particles are dispersed in one or more epoxy resins (such as diglycidyl ether of bisphenol A). For example, rubber particles are usually prepared in the form of an aqueous dispersion or emulsion. Such dispersions or emulsions can be combined with the desired epoxy resin or mixture of epoxy resins and water and other volatile substances removed by distillation, etc. A method for preparing such a masterbatch is described in more detail in International Patent Publication No. WO 2004 / 108825 (the disclosure of which is expressly incorporated herein by reference as a whole). For example, an aqueous latex of rubber particles can be contacted with an organic medium having partial solubility in water, and then contacted with another organic medium having a lower partial solubility in water than the first organic medium, to separate water and provide a dispersion of rubber particles in a second organic medium. Then, the dispersion can be mixed with one or more desired epoxy resins and volatile substances removed by distillation, etc., to provide a masterbatch.

[0109] Particularly suitable dispersions of rubber particles having a core-shell structure in an epoxy resin matrix are available from Kaneka Corporation.

[0110] For example, the core may be formed primarily of polybutadiene, polyacrylate, polybutadiene / acrylonitrile mixtures, polyols and / or polysiloxanes, or any other monomeric raw materials providing a low glass transition temperature. The shell may be formed primarily of polymethyl methacrylate, polystyrene or polyvinyl chloride, or any other monomeric raw materials providing a higher glass transition temperature.

[0111] The particle size of the core-shell rubber may be in the range of 0.07 μm to 10 μm, such as 0.1 μm to 5 μm.

[0112] The core-shell rubber made in this way can be dispersed in a thermosetting resin matrix (such as an epoxy resin matrix or a phenolic resin matrix). Examples of epoxy resin matrices include diglycidyl ethers of bisphenol A, F or S or bisphenol, novolac epoxy resins and alicyclic epoxy resins. Examples of phenolic resins include phenoxy based on bisphenol A. The matrix material is usually liquid at room temperature.

[0113] Based on viscosity considerations, the core-shell rubber dispersion may be present in an amount ranging from about 5 wt % to about 50 wt %, with about 15 wt % to about 25 wt % being desirable.

[0114] When used, these core shell rubbers allow toughening to occur in the composition and generally in a predictable manner (in terms of temperature neutrality to cure) due to the generally uniform dispersion that is typically observed in core shell rubbers when they are offered for commercial sale.

[0115] It is believed that many core-shell rubber structures available from Kaneka (such as those available under the KANEACE trade name) have a core made of a copolymer of (meth)acrylate-butadiene-styrene, wherein butadiene is the major component in phase-separated particles dispersed in an epoxy resin. Other commercially available masterbatches of core-shell rubber particles dispersed in epoxy resin include GENIOPERL M23A available from Wacker Chemie GmbH (a dispersion of 30 wt. % core-shell particles in an aromatic epoxy resin based on bisphenol A diglycidyl ether; the core-shell particles have an average diameter of about 100 nm and contain a crosslinked silicone elastomer core to which an epoxy-functional acrylate copolymer has been grafted; the silicone elastomer core accounts for about 65 wt. % of the core-shell particles).

[0116] In the case of those rubber particles that do not have such a shell, the rubber particles may be based on a core of such a structure.

[0117] Preferably, the size of the rubber particles is relatively small. For example, the average particle size can be about 0.03 μm to about 2 μm, or about 0.05 μm to about 1 μm. In certain embodiments of the present invention, the average diameter of the rubber particles is less than about 500 nm. In other embodiments, the average particle size is less than about 200 nm. For example, the average diameter of the rubber particles can be in the range of about 25 nm to about 200 nm, or about 50 nm to about 150 nm.

[0118] The rubber particles are generally composed of a material having elastomeric or rubber-like properties (i.e., a glass transition temperature below about 0°C, For exampleThe rubber particles may be composed of a polymer material having a temperature below about -30°C. For example, the rubber particles may be composed of a diene homopolymer or copolymer (e.g., a homopolymer of butadiene or isoprene, a copolymer of butadiene or isoprene and one or more ethylenically unsaturated monomers (e.g., vinyl aromatic monomers, (meth) acrylonitrile, (meth) acrylate, etc.)) and a polysiloxane. The rubber particles may contain functional groups (e.g., carboxylate groups, hydroxyl groups, etc.) and may have a linear, branched, cross-linked, random copolymer, or block copolymer structure.

[0119] For example, the rubber particles may be formed primarily from feedstocks of dienes (such as butadiene), (meth)acrylates, ethylenically unsaturated nitriles (such as acrylonitrile), and / or any other monomers that when polymerized or copolymerized produce polymers or copolymers having a low glass transition temperature.

[0120] The rubber particles may be used in dry form or may be dispersed in a matrix, as described above.

[0121] Generally, the composition may include from about 5% to about 35% by weight (in one embodiment, from about 15% to about 30% by weight) of rubber particles.

[0122] Combinations of different rubber particles can be advantageously used in the present invention. The rubber particles can differ, for example, in particle size, the glass transition temperature of their respective materials, whether they are functionalized, to what extent, with what materials they are functionalized, and whether and how their surfaces are treated.

[0123] A portion of the rubber particles may be provided in a masterbatch form (wherein the particles are stably dispersed in an epoxy resin matrix), while another portion may be provided to the adhesive composition in a dry powder form (i.e., without any epoxy resin or other matrix material). For example, a first type of rubber particles having an average particle diameter of about 0.1 μm to about 0.5 μm in dry powder form and a second type of rubber particles having an average particle diameter of about 25 nm to about 200 nm stably dispersed in a liquid bisphenol A diglycidyl ether matrix at a concentration of about 5 wt % to about 50 wt % may be used to prepare the adhesive composition. For example, the weight ratio of the first type of rubber particles: the second type of rubber particles may be about 1.5:1 to about 0.3:1.

[0124] The chemical composition of the rubber particles may be substantially uniform across all individual particles. However, the outer surface of the particles may be modified by reaction with coupling agents, oxidants, etc., in order to enhance the ability to disperse the rubber particles in the adhesive composition ( For exampleThe surface modification of the rubber particles can also enhance the adhesion of the epoxy resin matrix to the rubber particles when the adhesive is cured. The rubber particles can alternatively be irradiated to change the degree of crosslinking of one or more polymers constituting the rubber particles in different regions of the particles. For example, the rubber particles can be treated with gamma radiation so that the rubber is crosslinked to a greater degree near the surface of the particle than in the center of the particle.

[0125] Rubber particles suitable for use in the present invention can be obtained from commercial sources. For example, rubber particles provided by Eliokem, Inc., such as NEP R0401 and NEP R401S (both based on acrylonitrile / butadiene copolymers); NEP R0501 (based on carboxylated acrylonitrile / butadiene copolymers, CAS No. 9010-81-5); NEP R0601A (based on hydroxyl-terminated polydimethylsiloxane, CAS No. 70131-67-8); and NEP R0701 and NEP 0701S (based on butadiene / styrene / 2-vinylpyridine copolymers, CAS No. 25053-48-9) can be used. Also available are those under the PARALOID trade name (eg, PARALOID 2314, PARALOID 2300, and PARALOID 2600) from Dow Chemical Co., Philadelphia, PA, and those under the STAPHYLOID trade name (eg, STAPHYLOID AC-3832) from Ganz Chemical Co., Ltd., Osaka, Japan.

[0126] Rubber particles that have been treated with reactive gases or other reagents to modify the outer surface of the particles by, for example, establishing polar groups (e.g., hydroxyl groups, carboxylic acid groups) on the particle surface are also suitable for use in the present invention. Exemplary reactive gases include, for example, ozone, Cl2, F2, O2, SO3 and oxidizing gases. The method of surface-modifying rubber particles using such reagents is known in the art and is described in, for example, U.S. Patent Nos. 5,382,635, 5,506,283, 5,693,714 and 5,969,053 (each of which is incorporated herein by reference in its entirety). Suitable surface-modified rubber particles can also be obtained from commercial sources, such as the rubber sold by Exousia Corporation under the trade name VISTAMER.

[0127] When rubber particles are initially provided in dry form, it is advantageous to ensure that such particles are well dispersed in the adhesive composition before the adhesive composition solidifies. That is, the agglomerates of rubber particles are preferably pulverized to provide discrete independent rubber particles, which can be completed by homogeneous and thorough mixing of dry rubber particles and other components of the adhesive composition. For example, dry rubber particles can be blended with epoxy resin, and grinding or melt compounding reaches the following time length: it effectively disperses the rubber particles substantially completely and destroys any agglomeration of the rubber particles.

[0128] In addition, Nanoresins provides commercial products under the trade names ALBIDUR (epoxy resins containing core-shell silicone rubber particles, such as EP 2240, EP 2240A, EP 5340); ALBIFLEX (epoxy-siloxane block copolymer resins); and ALBIPOX (epoxy resins containing epoxy-nitrile butadiene rubber adducts). Some of these types of toughening agents can also be used in Part B of the composition. An example of one of these core-shell rubber particles is commercially available from Chemtura Corporation, Middlebury, CT under the trade name BLENDEX. In particular, BLENDEX 338 is an ultra-high rubber ABS impact modifier based on polybutadiene rubber.

[0129] Thickeners or viscosity modifiers are also useful. Useful materials in this regard include polyvinyl butyral resins sold under the trade name MOWITAL (Kuraray Ltd) (e.g. Mowital B30T, B60T, B20H, B30H, B45H, B60H, B30HH and B60HH).

[0130] Other additives may also be included in the Part A composition. For example, phosphoric acid may be included in the Part A composition. When included at a level of about 50 ppm to about 1000 ppm, such as about 100 ppm to about 500 ppm and applied to at least one aluminum substrate to be joined in the bonded assembly, improved strength and strength retention may be observed. More specifically, humidity, heat aging, and solvent immersion testing indicate that the addition of phosphoric acid to the two-part cyanoacrylate / cationically curable adhesive system of the present invention may result in significantly improved adhesives having excellent properties on both metals and plastics, particularly in terms of aluminum durability.

[0131] In another aspect, the invention relates to a method of bonding a substrate underwater, the method comprising:

[0132] Applying a cyanoacrylate composition underwater to at least one substrate, wherein the cyanoacrylate composition comprises:

[0133] a first part comprising a cyanoacrylate component and a cationic catalyst; and

[0134] The second part comprises:

[0135] a cationically curable component, such as an epoxy component, an episulfide component, an oxetane component, and combinations thereof, and an initiator component, and

[0136] The composition is allowed to cure underwater.

[0137] The cyanoacrylate composition may be applied wherein the ratio of the first part to the second part of the cyanoacrylate composition is from about 1:1 to about 10:1, such as 2:1 or 3:1 or 4:1, or 5:1 or 6:1 or 7:1 or 8:1 or 9:1.

[0138] The cyanoacrylate composition may be applied in a ratio of the first part to the second part in about a 1:1 ratio.

[0139] The method for bonding to the substrate under water can include exposing the composition to water for up to 45 seconds before the surface of the second substrate is engaged with the coated surface of the first substrate. This can be referred to as the open time of the composition. The composition can have a good open time of up to 90 seconds, for example, up to 60 seconds, for example, up to 45 seconds. Beneficially, the good open time allows time to correctly match the substrate before the composition solidifies. Since the good open time allows assembly time, the substrate can be assembled into an assembly with the correct configuration. The composition has a good open time, and allows the nozzle to be replaced underwater (by dispensing the composition with being applied to the nozzle) without curing the composition. The composition can form a film in the uppermost layer of the film, but is not solidified in the main body and has a good open time.

[0140] In the method for bonding to underwater substrate, the composition does not mix with water (e.g., in a water column), or is otherwise dispersed in water. The physical property of the composition (e.g., its viscosity) makes it not mix with water, and stays in the position to which it is applied. The outermost layer of the composition can be cured to form a film, and the film prevents the main body of the composition from contacting with water. In this respect, later on, after two substrates are combined together, solidification throughout the volume of the composition can occur.

[0141] The method of bonding a substrate under water may include curing a composition that can form a dielectric constant of at least 0.2 N / mm after curing for 24 hours. 2 For example, after curing for 168 hours, a pressure of 0.4 N / mm 2The bonding has a shear strength as measured according to ASTM D 1002. For example, when at least one substrate may comprise calcium carbonate, for example may be formed entirely or partially of calcium carbonate.

[0142] In a method of bonding a substrate under water, the composition is cured to form a strength of at least 0.2 N / mm after curing for 24 hours. 2 For example, after curing for 168 hours, a pressure of 0.4 N / mm 2 The invention relates to a bond having a shear strength as measured according to ASTM D1002. For example, when at least one substrate is formed of a metal (eg, steel).

[0143] In the methods of the present invention, one or both substrates may be naturally occurring and / or artificial.

[0144] Naturally occurring substrates include coral substrates (e.g., coral reefs). Coral reefs are formed by colonies of coral polyps. Calcium carbonate substrates can be bonded using the methods of the present invention. These substrates include coral substrates, such as calcium carbonate substrates, including the calcium carbonate skeleton of coral substrates. For example, the methods of the present invention can be used to repair damage in coral structures and / or add coral material to coral structures.

[0145] In the method of bonding substrates underwater, one or both substrates may be metal, for example one or both substrates may be steel.

[0146] In the method of bonding underwater substrates, at least one substrate may comprise a material selected from the group consisting of steel, aluminum, wood, fiberglass, building materials (including aggregates, sand, concrete / cementitious materials including iron slag cement), fiber reinforced plastics.

[0147] Suitably, both substrates may independently comprise a material selected from the group consisting of steel, aluminium, wood, glass fibre, building materials (including aggregates, sand, concrete / cementitious materials including iron slag cement), fibre reinforced plastics.

[0148] In the method of bonding substrates under water, at least one substrate may be a watercraft (such as a boat or ship) or a portion thereof. The method may be used to secure items to a boat or ship (e.g., to install sensors or attach replacement parts), or to perform repairs on a boat or ship. Using the method of the present invention, this may be done without having to return to land to remove the boat or ship from the water.

[0149] In the method of bonding underwater substrates, at least one substrate may be a structure located underwater or a portion of a structure extending underwater, such as a bridge, oil or gas rig equipment, pipeline, dam, wind turbine, or the like. Such structures cannot be removed from the water, so it is beneficial to be able to secure items (e.g., accessories, sensors) or replace parts or perform repairs underwater.

[0150] In methods of bonding underwater substrates, one or both substrates may comprise calcium carbonate, for example may be formed wholly or partly of calcium carbonate, for example one or both substrates are shells, for example one or both substrates are Scleractinia shells.

[0151] In methods of bonding substrates that are underwater, the nozzle life can be at least 4 minutes, such as at least 5 minutes. The dispensing nozzle has a good nozzle life because the composition does not prematurely cure and clog the nozzle. This is unexpected because compositions containing cyanoacrylates typically undergo rapid curing when exposed to moisture, such as when they are underwater. Advantageously, the nozzle life is increased and, therefore, allows more composition to be applied before the nozzle must be replaced.

[0152] The method of bonding a substrate under water can be performed in water containing varying amounts of salt and / or minerals. For example, the method can be performed in distilled water or treated water (e.g., a public / tap water supply). The method can be performed in fresh water (e.g., in a well, river, or lake). The method can be performed in salt water (e.g., in seawater, e.g., in water having a salinity of about 30 g / L to about 50 g / L).

[0153] The method of bonding a substrate underwater may be performed in water having a pH of about 6 to about 9, such as about 6.5 to about 8 or about 7.5 to about 8.5.

[0154] In another aspect, the invention relates to an assembly comprising two underwater substrates bonded together by the method of the invention. DETAILED DESCRIPTION

[0155] The method of bonding underwater substrates comprises applying the composition disclosed herein to at least one substrate underwater and curing the composition.

[0156] The nozzle service life may be at least 4 minutes, for example at least 5 minutes. This means that when the composition is applied, the composition will not solidify in the nozzle for dispensing at this time. It is possible that a thin layer of the composition may solidify at the tip of the nozzle where the composition is in contact with water. The bulk of the composition in the nozzle body that is not in contact with water will remain unsolidified. The composition will still be dispensed from the nozzle because the composition has a good nozzle service life under water.

[0157] Advantageously, the composition may be exposed to water for up to 45 seconds prior to joining the surface of the second substrate to the coated surface of the first substrate and the composition will remain uncured so that a bond can be formed between the substrates.

[0158] The method comprises curing the composition under water. The composition is not removed from the water for curing. When cured, the bond formed is strong. When cured, the bond formed maintains its strength over time, making the method of the present invention suitable for bonding substrates for a long time. The bond may have a strength of at least 0.2 N / mm after curing for 24 hours. 2 , for example, after curing for 168 hours, it has a strength of 0.4 N / mm 2 The shear strength as measured according to ASTM D1002 can be achieved with materials that are difficult to bond, such as calcium carbonate. Advantageously, bonding the calcium carbonate for a long time (e.g., 168 hours) makes the method suitable for applications in coral reefs, such as for coral transplantation. The bond strength achieved can be greater than the failure point of the calcium carbonate, meaning that the calcium carbonate will fail before the bond fails. The bond can have at least 0.2 N / mm after curing for 24 hours. 2 , for example, after curing for 168 hours, it has a strength of 0.4 N / mm 2 The shear strength as measured according to ASTM D1002. Bonds with higher shear strength can be achieved on substrates with higher shear strength because the substrate will not fail before the bond fails. For example, metals (e.g., steel, such as grit blasted mild steel (GBMS)) have higher shear strength than bonds formed by this method and can have a shear strength of at least 0.2 N / mm after curing for 24 hours. 2 , for example, after curing for 168 hours, it has a strength of 0.4 N / mm 2 Shear strength as measured according to ASTM D1002.

[0159] Example

[0160] Briefly, bonding of the substrates to be tested was performed as follows. The substrates were immersed in water so that the water was in contact with all surfaces of the substrate. The substrates were completely immersed. The substrates were not removed from the water prior to application of the adhesive.

[0161] The components of representative compositions of the present invention and numbered 1 to 5 are specified in Table 1. Each column gives the amount (in weight %) of each component in each of the five compositions.

[0162] Table 1

[0163]

[0164] *Add as stock solution

[0165] The composition numbered 3 with the components / amount listed in the column in the above table 1 is distributed from a container (with a 1:1 mixing ratio), and applied to the first substrate. One inch (2.54cm) of the second substrate is superimposed, and the substrates are clamped together, so that the adhesive is cured to form bonding between the substrates. The amount of time between distributing and superimposing the second substrate from the container is the open time. The application of the adhesive and the curing of the adhesive are both carried out underwater. In order to test dry substrates, substrates are not placed underwater. When applying adhesive and when the adhesive is cured, substrates are dry (that is, without surface moisture). The shear strength of bonding is measured according to ASTM D1002.

[0166] The following substrates were tested: Grit blasted mild steel (GBMS), Calcium carbonate.

[0167] result

[0168] GBMS substrates were bonded with an open time of 0 seconds. That is, the composition was applied to the substrate and the substrates were immediately joined together. The substrates were not removed from the water while the adhesive cured. The bond was cured while fully submerged in water. The results are shown in Table 2. The strength achieved allows manipulation of the bonded substrates without bond failure. After curing for 24 hours, the bond strength was maintained, as shown in Table 2. After curing for 168 hours, the bond strength was maintained, as shown in Table 2.

[0169] The calcium carbonate substrate was bonded with an open time of 0 seconds. The substrate was not removed from the water while the adhesive was curing. The bonding was cured while fully immersed in water. As shown in Table 2, after curing for 5 minutes, the adhesive achieved good handling strength. This strength allows handling of the bonded substrate without adhesive failure. After curing for 24 hours, the bond strength was maintained, as shown in Table 2. After curing for 168 hours, the bond strength was maintained, as shown in Table 2.

[0170] Table 2

[0171]

[0172] When adhesive is distributed once every 2 minutes or less, the nozzle service life of the packaging of underwater adhesive is greater than 5 minutes. Table 3 shows that the adhesive composition is easy to distribute and does not block the nozzle after 5 minutes. The adhesive composition is easily squeezed out from the nozzle at 0 minutes (that is, when the nozzle is initially open to water). After 1 minute of opening to water, the composition is easily squeezed out from the nozzle. The nozzle under water does not prevent the distribution of the composition. After another minute (2 minutes) under water, the composition is easily distributed from the nozzle. After another minute (3 minutes) under water, the composition is easily distributed from the nozzle. After another 2 minutes (5 minutes) under water, because the surface of the composition has begun to solidify, the tip of the nozzle needs to be cleaned. There is no main body solidification of the composition, only the thin layer of the composition has begun to solidify. The tip of the cleaning nozzle is to remove the solidified layer, and because there is no main body solidification, the composition is easily distributed from the nozzle.

[0173] Table 3

[0174] Time (min) Nozzle service life 0 Easy to distribute 1 Easy to distribute 2 Easy to distribute 3 Easy to distribute 5 Requires tip cleaning, easy to dispense

[0175] When used herein in relation to the present invention, the words “include / comprise” and the words “have / contain” are used to specify the presence of stated features, integers, steps or components, but do not preclude the presence or addition of one or more other features, integers, steps, components or groups thereof.

[0176] It should be understood that certain features of the present invention described in the context of separate embodiments for the sake of clarity may also be provided in combination in a single embodiment. Conversely, the various features of the present invention described in the context of a single embodiment for the sake of brevity may also be provided separately or in any suitable sub-combination.

Claims

1. A method for bonding a substrate underwater, the method comprising: Applying a cyanoacrylate composition underwater to at least one substrate, wherein the cyanoacrylate composition comprises: (a) a first part, the first part comprising: a cyanoacrylate component and a cationic catalyst; and (b) a second part, the second part comprising: Cationic curable components such as epoxy components, episulfide components, oxetane components, and combinations thereof, and an initiator component, and The composition is allowed to cure underwater.

2. The method according to claim 1, wherein the cyanoacrylate component of the cyanoacrylate composition is selected from the group consisting of substances within the structure H2C=C(CN)-COOR, wherein R is selected from C 1-15 Alkyl, C 2-15 Alkoxyalkyl, C 3-15 Cycloalkyl, C 2-15 Alkenyl, C 6-15 Aralkyl, C 5-15 Aryl, C 3-15 Allyl and C 1-15 Haloalkyl, for example, wherein the cyanoacrylate component comprises ethyl 2-cyanoacrylate.

3. A method according to any preceding claim, wherein the cationic catalyst comprises a salt of lithium and a salt of a metal of Group II of the Periodic Table, and a non-nucleophilic acid.

4. The method of claim 3, wherein the cationic catalyst is a non-nucleophilic acid having a pH of less than 1.0 when measured as a 10 wt% aqueous solution.

5. The method according to any preceding claim, wherein the cationic catalyst is a member selected from the group consisting of fluoroboric acid, fluoroarsenic acid, fluoroantimonic acid, and fluorophosphoric acid; lithium tetrafluoroborate, calcium bis(tetrafluoroborate), magnesium bis(tetrafluoroborate), lithium hexafluorophosphate, calcium bis(hexafluorophosphate), magnesium bis(hexafluorophosphate), lithium hexafluoroantimonate, and lithium hexafluoroarsenate; lanthanide trifluoromethanesulfonates, aryl iodonium salts, aryl sulfonium salts, lanthanum trifluoromethanesulfonate, ytterbium trifluoromethanesulfonate, trimethoxycyclotriboroxane, trimethoxycyclotriboroxane-aluminum acetylacetonate, amine-boron trihalide complexes, quaternary ammonium salts, quaternary phosphonium salts, triaryl sulfonium salts, diaryl iodonium salts, and diazonium salts; trialkoxycyclotriboroxane curing agents; and combinations thereof.

6. The method of any preceding claim, wherein the cationically curable component is selected from the group consisting of epoxy components, episulfide components, oxetane components, vinyl ether components, and combinations thereof.

7. A method according to any preceding claim, wherein the cationically curable component is an epoxy component selected from the group consisting of cycloaliphatic epoxy resins, aromatic epoxy resins, aliphatic epoxy resins and hydrogenated aromatic epoxy resins.

8. The method of any preceding claim, wherein the cationically curable component is an epoxy component and the epoxy component comprises a member selected from the group consisting of epoxy-functionalized hydrogenated bisphenol A, bisphenol F, bisphenol E, bisphenol S, and biphenyl.

9. A method according to any preceding claim, wherein the first portion further comprises phosphoric acid.

10. The method of any preceding claim, wherein the second part further comprises at least one of a plasticizer, a filler, and a toughening agent.

11. The method of claim 10, wherein the toughening agent is a member selected from the group consisting of: (1) (a) a reaction product of a combination of ethylene, methyl acrylate, and a monomer having a carboxylic acid cure site; (2) (b) a binary copolymer of ethylene and methyl acrylate; (3) a combination of (a) and (b); (4) a vinylidene chloride-acrylonitrile copolymer; (5) a vinyl chloride / vinyl acetate copolymer; (6) a copolymer of polyethylene and polyvinyl acetate; and combinations thereof.

12. A method according to any preceding claim, wherein the first part and the second part are present in a ratio of about 1 :1 by volume.

13. A method according to any preceding claim, wherein the initiator component is a member selected from the group consisting of heterocycles, pyridines, benzothiazoles, toluidines and phenols.

14. The method according to any preceding claim, wherein the initiator component is a member selected from the group consisting of 3,5-dibromopyridine, 3,5-dichloropyridine, N,N-dimethyl-p-toluidine, 2,2-dipyridyl disulfide, 5-chloro-2-methylbenzothiazole, 2-methyl-mercaptobenzothiazole, N,N-dihydroxyethyl-p-toluidine, tert-butylbenzothiazole sulfonamide, 4-methyl-2,2-di-tert-butylphenol and 4-methoxyphenol.

15. A method according to any preceding claim, wherein one or both substrates is metal, for example one or both substrates is steel.

16. A method according to any preceding claim, wherein one or both substrates comprises calcium carbonate, for example one or both substrates are shells, for example one or both substrates are Scleractinia shells.

17. A method according to any preceding claim, wherein the nozzle service life is at least 4 minutes, such as at least 5 minutes.

18. An assembly comprising two underwater substrates bonded together by a method according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Filled cyanoacrylate adhesive compositions

    US4102945A

  • Epoxy adhesive composition

    US4336367A

  • Particle agglomeration in rubber latices

    US4419496A

  • Toughened cyanoacrylates containing elastomeric rubbers

    US4440910A

  • Adhesive cyanoacrylate compositions with reduced adhesion to skin

    US4444933A